Correlation of serum ferritin, LDH, CRP with chest findings- CT severity index in COVID-19 patients - Bansal, Ankush; Gupta, Aayushi; Lachyan, Abhishek; Choudhary, Dhirender; Sharma, Roshni; Dhania, Swati; Bansal, Aman (International Journal Of Community Medicine And Public Health, 2023)
Background: The COVID-19 pandemic is caused by a highly infectious virus primarily transmitted from person to person. The initial clinical manifestations of the condition are non-specific, characterized by the presence of fever and cough. These symptoms may resolve independently or escalate to acute respiratory distress syndrome (ARDS), multiple organ failure, and ultimately, mortality. Methods: The research was conducted at Moolchand Khairatiram Hospital in the COVID-19 wards and ICU in New Delhi. The blood samples were collected and then analyzed to evaluate the following parameters: C-reactive protein (CRP), serum ferritin, and LDH are the three biomarkers of interest. The statistical significance threshold was established at a p value of less than 0.05. Results: The study included 200 patients, 49% of whom were male and 51% of whom were female. A link was discovered between the outcome and the CT severity index. Patients who had a CT severity index of 21-25 died at the highest rate. The CT severity index and ferritin were found to have a significant relationship, with patients with elevated ferritin levels reporting the highest CT severity index scores. Conclusions: A statistically significant association was observed between the CT severity index and the outcome, with the highest mortality rate observed in patients who had a CT severity index of 21-25. The parameters above are crucial in assessing the condition and predicting the outcome of individuals afflicted with COVID-19.